Membersihkan Salah Faham Terhadap Dakwah Syaikh Muhammad bin Abdul Wahhab. - Abdul Aziz Muhammad Ali Al-Abdul Al-Lathif 432844, author; Mohammad Amin Yaacob 635646, translator (Johor : Perniagaan Jahabersa, 2009)
Includes bibliographical references.